2019
DOI: 10.32614/rj-2019-010
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Positioning and Fingerprinting: The R Package ipft

Abstract: Methods based on Received Signal Strength Indicator (RSSI) fingerprinting are in the forefront among several techniques being proposed for indoor positioning. This paper introduces the R package ipft, which provides algorithms and utility functions for indoor positioning using fingerprinting techniques. These functions are designed for manipulation of RSSI fingerprint data sets, estimation of positions, comparison of the performance of different positioning models, and graphical visualization of data. Well-kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This method estimates the location of the test fingerprint by averaging the known locations of the K-nearest fingerprints in the radio map. KNN (k = 3) classification was performed using the ‘ipfKnn’ and ‘ipfEstimate’ functions from the ipft package in R (Sansano et al, 2019). As we had no prior expectation of the ideal choice of k and exploratory analysis suggested that different values did not impact the localisation accuracy, we used the default value (3) from the ‘ipfKnn’ function and the Euclidean distance between fingerprints was calculated to determine similarity.…”
Section: Methodsmentioning
confidence: 99%
“…This method estimates the location of the test fingerprint by averaging the known locations of the K-nearest fingerprints in the radio map. KNN (k = 3) classification was performed using the ‘ipfKnn’ and ‘ipfEstimate’ functions from the ipft package in R (Sansano et al, 2019). As we had no prior expectation of the ideal choice of k and exploratory analysis suggested that different values did not impact the localisation accuracy, we used the default value (3) from the ‘ipfKnn’ function and the Euclidean distance between fingerprints was calculated to determine similarity.…”
Section: Methodsmentioning
confidence: 99%
“…In the fingerprintbased method, a specific location P(x, y) is assigned to a distinct fingerprint. Any information helping to distinguish a location can be used as a fingerprint; e.g., if every location has a unique temperature, this temperature may be considered as a fingerprint (Sansano, E. et al [43]). Normally, RSSI values are usually used as fingerprints in engineering.…”
Section: Related Workmentioning
confidence: 99%
“…This is a technology that has already awakened but that in a short period of time will suffer a big explosion, as happened with the systems of positioning by satellite in exteriors and its applications. This paper introduces the R package ipft (Sansano, 2017), a collection of algorithms and utility functions to create models, make estimations, analyze and manipulate RSSI fingerprint data sets for indoor positioning. Given the abundance of potential applications for indoor positioning, the package may have a broad relevance in fields such as pervasive computing, Internet of Things (IoT) or healthcare, among many others.…”
Section: Introductionmentioning
confidence: 99%